Chronic sazetidine‐A maintains anxiolytic effects and slower weight gain following chronic nicotine without maintaining increased density of nicotinic receptors in rodent brain. (7th February 2014) - Hussmann, G. Patrick; DeDominicis, Kristen E.; Turner, Jill R.; Yasuda, Robert P.; Klehm, Jacquelyn; Forcelli, Patrick A.; Xiao, Yingxian; Richardson, Janell R.; Sahibzada, Niaz; Wolfe, Barry B.; Lindstrom, Jon; Blendy, Julie A.; et al.
Abstract Chronic nicotine administration increases the density of brain α4β2* nicotinic acetylcholine receptors (nAChRs), which may contribute to nicotine addiction by exacerbating withdrawal symptoms associated with smoking cessation. Varenicline, a smoking cessation drug, also increases these receptors in rodent brain. The maintenance of this increase by varenicline as well as nicotine replacement may contribute to the high rate of relapse during the first year after smoking cessation. Recently, we found that sazetidine‐A (saz‐A), a potent partial agonist that desensitizes α4β2* nAChRs, does not increase the density of these receptors in brain at doses that decrease nicotine self‐administration, increase attention in rats, and produce anxiolytic effects in mice. Here, we investigated whether chronic saz‐A and varenicline maintain the density of nAChRs after their up‐regulation by nicotine. In addition, we examined the effects of these drugs on a measure of anxiety in mice and weight gain in rats. After increasing nAChRs in the rodent brain with chronic nicotine, replacing nicotine with chronic varenicline maintained the increased nAChR binding, as well as the α4β2 subunit proteins measured by western blots. In contrast, replacing nicotine treatments with chronic saz‐A resulted in the return of the density of nAChRs to the levels seen in saline controls. Nicotine, saz‐A and varenicline each demonstrated anxiolytic effects in mice, but only saz‐A and nicotine attenuated the gain of weight over a 6‐week period in rats. These findings suggest that apart from its modest anxiolytic and weight control effects, saz‐A, or drugs like it, may be useful in achieving long‐term abstinence from smoking. <boxed-text content-type="graphic" id="jnc12652-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> Chronic treatment with nicotine increases brain α4β2 nicotinic receptors, which may be related to nicotine addiction. When nicotine is replaced by varenicline, this receptor increase is maintained; in contrast, when nicotine is replaced by sazetidine‐A the receptors return to baseline levels. The doses of drugs used here are anxiolytic and slow gain of body weight compared to saline controls.